EXAMINING OF SHORT CHAIN FATTY ACIDS - METABOLITES OF PERIODONTAL PATHOGENIC FLORA - AS MARKERS OF DIAGNOSTIC OF MICROBIOCENOSIS OF ORAL CAVITY - O.L. Lychkovska; G.M. Melnychuk (Ukrainian Medical Stomatological Academy, 2017)
Introduction. It has been established thus far that periodontal pathogenic flora is the leading factor in the development of generalized periodontitis (GP) as it produces endotoxins, proteolytic enzymes, as well as short chain fatty acids (SCFA), which have significant damaging potential for periodontal tissues. The object of the research is to examine content and ratio of the short chain fatty acids in oral fluid of patients with generalized periodontitis (GP) at the initial-I and I-II stage of development. Materials and methods. Seventy-eight persons aged between 20 and 44 years old without somatic diseases, including 18 healthy persons and 60 with (GP) disease with chronicity at the initial (30) and I-II (30) stage of development were examined. State of microbiocoenosis in oral cavity was assessed indirectly by identifying metabolites of bacteria, namely SCFA in oral fluid using the method of gas-liquid chromatography. The qualitative and quantitative content of SCFA in oral fluid was examined at the gas-liquid chromatograph Shimadzu GC 2014. Absolute concentration of acetic, propionic, butyric, and caproic acids was estimated, as well as total content of the short chain fatty acids with unbranched chain, anaerobic index (AI), and total concentration of isoacids (isobutyric, isovalerianic, and isocaproic). Research results and discussions. Concentration of the unbranched SCFA was changing significantly in oral cavity of patients with GP as follows: level of acetic acid was decreasing, while the content of propionic, butyric, and caproic acids was increasing, especially in case of GP at the I-II stage of development. These data reflect the suppression of aerobic flora associated with the growing activity of anaerobic microflora, namely genuses of Clostridium, Bacteroides, and Fusobacterium. Increasing concentration of butyric acid is probably indicative not only of the involvement of bacteroides and propionibacteria into the inflammation period, but also bacteria of the Clostridium genus, by highlighting the deterioration of the state of microbiocenosis. Total content of the SCFA and the AI in patients with GP was increasing significantly, especially in case of GP at the I-II degree, which testified to growth in the number of periodontopathogens in oral cavity. Total content of isoacids in case of GP was increasing, but not significantly; it reflects the growth in the processes of proteolysis in oral cavity, for which the aerobic link of microbiocenosis is more responsible than anaerobic one. Conclusions. Concentration of the unbranched SCFA was changing significantly in oral cavity of patients with GP as follows: level of acetic acid was decreasing (p<0,05; p<0,001), while the content of propionic, butyric, and caproic acids was increasing (p<0,001), especially in case of GP at the I-II stage of development. Total content of the SCFA and the AI in patients with GP was increasing significantly, especially in case of GP at the I-II degree (p<0,001), which testified to growth in the number of periodontopathogens in oral cavity. Total content of isoacids in case of GP was increasing, but not significantly (p>0,05); it reflects the growth in the processes of proteolysis in oral cavity, for which the aerobic link of microbiocenosis is more responsible than anaerobic one. Examining the SCFA with the method of gas-liquid chromatography enables to diagnose indirectly the malformation of microbiocenosis of oral cavity in patients with GP in view of reducing the time and financial expenditures. So, one can say, its simplicity and quickness, achievement of the results are main advantages of usage of this method.